(untitled) (Cadernos de Sociomuseologia, 2014)
This study focuses on the theoretical relationship between Museology, most precisely Sociomuseology, and the analytic category of Gender, relation that we try to clarify by analyzing women’s images in exhibitions in some Portuguese museums. At a time when the concern for gender equality is increasingly present in the formulation of public policies and in the development of projects aimed at the equal valorization of the contribution of men and women in society, it is urgent that museology looks into this matter. To relate museology (focusing on aspects of sociomuseology) with the analytic category of gender and to understand the impact this inclusion will have on methodology, field of study and theoretical corpus of museology, relates itself with those general concerns and the contemporary trends of museology performance. By addressing the issue of gender in a feminine perspective, we research women’s images in museum exhibitions, trying to understand if these images perpetuate social stereotypes and social categories of women that promote inequality and the distinct social valorization of women compared to men. Keywords: Museology, Sociomuseology, Gender Equality, Woman, Inclusion